Хірургічне лікування пухлин надниркових залоз у дітей і підлітків - Черенько, С. М.; Ларін, О. С.; Товкай, О. А. (Clinical Endocrinology and Endocrine Surgery, 2008)
Among 385 adrenalectomy performed at the Ukrainian Scientific and Practical Centre of Endocrine Surgery during 1996-2008 years 23 (6%) operations have been done for patients no older than 18 years. Eleven children (48 %) were operated by laparoscopic approach and twelve children (52 %) — by open adrenalectomy. It is possible to perform a radical laparoscopic adrenalectomy in most cases of benigne adrenal tumors in children and adolescents using operation’s technology, which was elaborated for adults, but taking into account a child organism peculiarities.